Afterlives of the Clouded Leopard: Likulau Heirlooms and Paiwan Culture - Lemaitre, Agathe (Humanimalia, 2023)
This paper analyses the afterlives of the likulau (clouded leopard), through its spiritual presence and material traces among the indigenous Paiwan people of Taiwan. Despite having been locally extinct for over half a century, the clouded leopard still continues to inhabit the myths and imaginations of the local population. In traditional Paiwan culture, the clouded leopard held a special status, and its skin and teeth were used to make ritual clothes and adornments for the village chiefs. In this paper, I explore the significance of these likulau artefacts in contemporary Paiwan society. I also examine how the Paiwan’s interactions with and the cultural significance of these objects have evolved in connection with environmental changes and social transformations of Paiwan society. As embodied in these material traces, the clouded leopard is both absent and present, extinct and alive. I explore this spectral presence via the concept of survivance (Didi-Huberman), examining how the ambiguous persistence of the clouded leopard relates to the resilience of traditional Paiwan culture.